The International Legal Responsibility of Pharmaceutical Companies for Human Rights Violations - Aslan H. Abashidze; Vladislav S. Malichenko (Московский журнал международного права, 2014)
The pharmaceutical sector plays an important role in ensuring the right to health by creating conditions for access to medicines. However, the policy and practice of a number of big pharmaceutical companies creates additional problems for the States in realisation of citizens’ rights to the highest attainable standard of health and as a result interferes with their efforts to ensure access to medicines. In contemporary international law there are virtually no provisions allowing making pharmaceutical companies accountable for human rights violations. However, in a growing number of human rights violations on the part of pharmaceutical companies and the lack of effective national legal remedies, the need of an effective international mechanism, which will take into account the national experience acquired in this fi eld and make pharmaceutical companies accountable for violations of human rights, becomes increasingly apparent.